Basic Robotecnical Platform for Implementation of Accurate Farming Technologies - N. I. Tchernyshev; O. E. Sysoev; D. B. Solovev; E. P. Kiselyov (Institute of Advanced Engineering and Science, 2018)
Improvement of modern technical systems and technologies. Increasing the productivity of modern agricultural machines with increasing their weight, which leads, in the course of their work, to a significant compaction of the soil. The heterogeneity of the soil, as a bearing surface, causes not adjustable fluctuations in the workplace, which makes automation of the application of robotics more difficult. Modern solutions to the problems of reducing the negative impact on the soil, increasing the permeability of aggregates due to the reconstruction of the propulsors do not give the proper effect. More cardinally solve these problems, as well as the ability to implement automation and robotics bridge systems such as ABAC, moving along rail tracks, AASP on vertical piles and point gravel-halide supports with concrete platforms. The most promising of these is the AAS platform, which is a 30x10 m bridge structure that moves by step-by-step extension, the beams onto 3 subsequent pads located 10 m away. After entering the new position of the bridge platform, along the long 30-meter span beams Moves the work-technological module with a set of working elements, performing the programmed operations. Thus, in the AASP bridge system under consideration, the soil area subjected to compaction at reference points is just over 1% of the 70% protraction of modern machines. Compared to the ABAC system, moving along railways, the equipment of point supports is much less expensive and requires insignificant operating costs. At the same time, the rigidity of AASP design ensures stable operation of technological mechanisms in a programmed robotic mode with a minimum of unproductive energy costs associated with movement.